2016
DOI: 10.1007/s12687-016-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Translation and adaptation of skin cancer genomic risk education materials for implementation in primary care

Abstract: Genomic medicine has revolutionized disease risk identification and subsequent risk reduction interventions. Skin cancer risk genomic feedback is a promising vehicle to raise awareness and protective behaviors in the general population, including Hispanics who are largely unaware of their risks. Yet, personalized genomics currently has limited reach. This study is the initial phase of a randomized controlled trial investigating the personal utility and reach of genomic testing and feedback for melanoma. Semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…More research is needed to explore barriers to genomic testing among racially and ethnically diverse and less educated patients, including lack of knowledge, lower genomic literacy, and lack of confidence in the medical system, to achieve maximum benefits of precision prevention for skin cancer and other chronic diseases in the broad population who stand to benefit from such technologies. In the current study, we conducted translation of all our study materials into New Mexican Spanish and conducted preliminary qualitative research to confirm the comprehensibility and acceptability of these materials 38 ; yet further efforts to understand important barriers clearly remain. Comparatively lower interest in diverse populations might create or perpetuate health disparities in this population, and key factors that predict existing health disparities in this population might also be barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is needed to explore barriers to genomic testing among racially and ethnically diverse and less educated patients, including lack of knowledge, lower genomic literacy, and lack of confidence in the medical system, to achieve maximum benefits of precision prevention for skin cancer and other chronic diseases in the broad population who stand to benefit from such technologies. In the current study, we conducted translation of all our study materials into New Mexican Spanish and conducted preliminary qualitative research to confirm the comprehensibility and acceptability of these materials 38 ; yet further efforts to understand important barriers clearly remain. Comparatively lower interest in diverse populations might create or perpetuate health disparities in this population, and key factors that predict existing health disparities in this population might also be barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified potential barriers to genetic risk communication in Hispanics, such as health literacy, language, and access 36 , as well potential facilitators of use such as a cultural orientation prioritizing family relationships and communication 37 . All RCT study materials (website, risk feedback, surveys) were available in Spanish as well as English 38 .…”
Section: Introductionmentioning
confidence: 99%
“…If any issues were raised by at least one participant, a research assistant or the investigator panel (multidisciplinary team composed of experts in qualitative data analysis, linguistic translation, health and genetic literacy, and anthropology) evaluated the item for revision and labeled it as a problem [ 90 ]. Procedural details and results are reported elsewhere [ 91 ]. Most materials were comprehensible and acceptable, but 33 of 246 terms/concepts were not.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from these three studies, all designed to assess behavior changes out to one year post-intervention, are expected over the next several years. Of note, the two ongoing studies in the United States have incorporated a core content of shared risk feedback materials, including Spanish translations (23), and there is a healthy cross-fertilization of idea and practice experience across the investigators of all three ongoing studies.…”
Section: Ongoing Research Investigating Mc1r As a Genetic Risk Screenmentioning
confidence: 99%